MARKETING MIX AND CUSTOMER PERCEPTION TOWARDS PLASTIC FURNITURE IN VAVUNIYA DISTRICT - Udeshini, R.; Pushpanathan, A. (South Eastern University of Sri Lanka, 2013)
This study attempts to analyze the impact of marketing mix and buyer’s characteristics on consumer perception towards plastic furniture in Vavuniya District. The marketing mix variables such as product, price, place and promotion were considered as independent variable and consumer perception (Decision making process) was considered as dependent variable. This study utilized one hundred customers, based on divisional secretariats in Vavuniya District from four divisions on the basis of random sampling method .Data were analyzed by using the SPSS 17 package and percentage analysis to measure to what extend the dimension of marketing mix influence on customer perception of plastic furniture. The overall result of this study indicated that there was a positive relationship observed between marketing mix and consumer perception (β=0.768.p<0.01 respectively) and 88% of consumers agreed that the marketing mix was highly influence on the consumer perception towards plastic furniture in Vavuniya district.
Keywords: Customer perception; Consumer preference; Marketing Mix; Plastic furniture